Evaluación de la calidad microbiológica en salchichas de pollo que se expenden en el mercado cerrado en la ciudad de Latacunga. - Cisneros Corrales, Jessica Dayana (2022)
Chicken sausages are a cooked-meat product classified as sausages. In Ecuador, it is a food for daily consumption that is purchased in different supply places such as a public market, neighborhood stores, supermarkets, mini commissaries, among others. The market is the place where chicken sausages are sold and it is unknown if this product is microbiologically suitable for human consumption, and if it does not represent a health risk. The objective of this current research work is to determine the microbiological quality in chicken sausages that are sold in the closed market of the city of Latacunga. The analysis was carried out under the INEN NTE 1338:2012 standard, which specifies the microbiological conditions that this product must meet for its consumption. The presence or absence of Salmonella and the cfu/g count for E. coli, S. aureus, coliforms and aerobic mesophiles were analyzed by using Petrifilm Plates. The results in the E. coli count were <10 cfu/g, in coliforms an average of 101 cfu/g, in S. aureus an average of 101 cfu/g, and for aerobic mesophiles 102 cfu/g. In the analysis of the absence and presence of Salmonella, it was established that 50% of the samples comply with the regulations. It is concluded that the analyzed samples comply with the parameters established at acceptable levels in the regulations for both E. coli, S. aureus, coliforms, and aerobic mesophiles except for Salmonella and due to the presence of this bacterium, the product is rejected; therefore, it is not microbiologically fit for consumption.